A Robust 3D Cage‐like Ultramicroporous Network Structure with High Gas‐Uptake Capacity. (27th February 2018) - Mahmood, Javeed; Kim, Seok‐Jin; Noh, Hyuk‐Jun; Jung, Sun‐Min; Ahmad, Ishfaq; Li, Feng; Seo, Jeong‐Min; Baek, Jong‐Beom
Abstract: A three‐dimensional (3D) cage‐like organic network (3D‐CON) structure synthesized by the straightforward condensation of building blocks designed with gas adsorption properties is presented. The 3D‐CON can be prepared using an easy but powerful route, which is essential for commercial scale‐up. The resulting fused aromatic 3D‐CON exhibited a high Brunauer–Emmett–Teller (BET) specific surface area of up to 2247 m 2  g −1 . More importantly, the 3D‐CON displayed outstanding low pressure hydrogen (H2, 2.64 wt %, 1.0 bar and 77 K), methane (CH4, 2.4 wt %, 1.0 bar and 273 K), and carbon dioxide (CO2, 26.7 wt %, 1.0 bar and 273 K) uptake with a high isosteric heat of adsorption (H2, 8.10 kJ mol −1 ; CH4, 18.72 kJ mol −1 ; CO2, 31.87 kJ mol −1 ). These values are among the best reported for organic networks with high thermal stability (ca. 600 °C).